A pilot hole does not reduce the strains or risk of fracture to the lateral cortex during and following a medial opening wedge high tibial osteotomy in cadaveric specimens. Issue 2 (February 2018) - Bujnowski, K.; Getgood, A.; Leitch, K.; Farr, J.; Dunning, C.; Burkhart, T. A.
Abstract : Aim: It has been suggested that the use of a pilot-hole may reduce the risk of fracture to the lateral cortex. Therefore the purpose of this study was to determine the effect of a pilot hole on the strains and occurrence of fractures at the lateral cortex during the opening of a high tibial osteotomy (HTO) and post-surgery loading. Materials and Methods: A total of 14 cadaveric tibias were randomized to either a pilot hole (n = 7) or a no-hole (n = 7) condition. Lateral cortex strains were measured while the osteotomy was opened 9 mm and secured in place with a locking plate. The tibias were then subjected to an initial 800 N load that increased by 200 N every 5000 cycles, until failure or a maximum load of 2500 N. Results: There was no significant difference in the strains on the lateral cortex during HTO opening between the pilot hole and no-hole conditions. Similarly, the lateral cortex and fixation plate strains were not significantly different during cyclic loading between the two conditions. Using a pilot hole did not significantly decrease the strains experienced at the lateral cortex, nor did it reduce the risk of fracture. Conclusions: The nonsignificant differences found here most likely occurred because the pilot hole merely translated the stress concentration laterally to a parallel point on the surface of the hole. Cite this article : K. Bujnowski, A. Getgood, K. Leitch, J. Farr, C. Dunning, T. A. Burkhart. A pilot hole does not reduce the strains or risk of fracture to the lateral cortex during and following a medial opening wedge high tibial osteotomy in cadaveric specimens. Bone Joint Res 2018;7:166–172. DOI: 10.1302/2046-3758.72.BJR-2017-0337.R1.